Ratio Analysis of Financials and Stock Price of Heavy Construction and Civil Engineering Companies - Maria Felsiani Melan; Eni Lisetyati; Retna Safriliana (Journal of Research on Business and Tourism, 2023)
The goal of this research is to assess the influence of financial ratios like Current Ratio, Total Asset Turnover, Debt to Equity Ratio, and Return on Equity on stock prices that are calculated using closing prices. Moreover, the data used for this study is taken from the financial statements of Heavy Construction and Civil Engineering Companies listed on the Indonesia Stock Exchange (IDX) within the time frame of 2017 to 2021.In the research project there are 23 Heavy Construction and Civil Engineering Companies involved. The selection process for the sample includes choosing 10 companies based on predetermined criteria using a purposive sampling method. Stock Price is considered as the dependent variable, while the independent variables consist of Current Ratio, Total Asset Turnover, Debt to Equity Ratio, and Return on Equity. The chosen data analysis method for this study is employing multiple linear regression. This approach encompasses conducting descriptive analysis as well as assessing classical assumptions. Moreover, it involves performing multiple linear regression analysis while using an F-test for evaluating the model fit alongside t-tests for testing hypotheses. Also, the determination coefficient is calculated in order to determine the percentage of influence exerted by the independent variables on the dependent variable.